Correlation of Body composition, Physical activity with aging: a cross-sectional study for urban adult Indian women (Journal of Food and Dietetics Research, 2023)
With simple random sampling technique for 450 women of age group 41-55 years, with the general objective of finding out the relationship between Body composition, Physical activity with aging in Gwalior city of India ,descriptive cross-sectional study was conducted . The group was further subdivided into three age groups of 41-45, 46-50, and 51-55 years. Hypothesis testing F test and Correlation were applied to analyze the data.There was significant difference in Body fat percentage score across the three subgroups (p = 0.030). The high mean body mass index (BMI-27.31 (±4.8)) for the total population is an alarming indication for the increasing overweight population in India. The same was supported by a higher average waist-hip ratio of 0.87. The mean weight of 450 women was 65.3 kg (±11.5).GPAQ score differed significantly across the three age groups (p = 0.000).With very high contribution in GPAQ score from house works, majority of the women were found moderately physically active and Sports, fitness and recreational activities were found very less. The older age group was found less physically active. The Findings were that body fat% were positively correlated (p
Keywords: Body composition; Physical activity; Ageing; BMI; GPAQ